An improved LC‐MS/MS method for quantitation of indapamide in whole blood: application for a bioequivalence study. (22nd April 2014) - Pinto, Guilherme Araújo; Pastre, Kátia Isabel Fercondini; Bellorio, Karini Bruno; de Souza Teixeira, Leonardo; de Souza, Weidson Carlo; de Abreu, Fernanda Crunivel; de Santana e Silva Cardoso, Fabiana Fernandes; Pianetti, Gerson Antônio; César, Isabela Costa
ABSTRACT An improved LC‐MS/MS method for the quantitation of indapamide in human whole blood was developed and validated. Indapamide‐d3 was used as internal standard (IS) and liquid–liquid extraction was employed for sample preparation. LC separation was performed on Synergi Polar RP‐column (50 × 4.6 mm i.d.; 4 µm) and mobile phase composed of methanol and 5 mm aqueous ammonium acetate containing 1 mm formic acid (60:40), at flow rate of 1 mL/min. The run time was 3.0 min and the injection volume was 20 μL. Mass spectrometric detection was performed using electrospray ion source in negative ionization mode, using the transitions m/z 364.0 → m/z 188.9 and m/z 367.0 → m/z 188.9 for indapamide and IS, respectively. Calibration curve was constructed over the range 0.25–50 ng/mL. The method was precise and accurate, and provided recovery rates >80% for indapamide and IS. The method was applied to determine blood concentrations of indapamide in a bioequivalence study with two sustained release tablet formulations. The 90% confidence interval for the geometric mean ratios for maximum concentration was 95.78% and for the area under the concentration–time curve it was 97.91%. The tested indapamide tablets (Eurofarma Laboratórios S.A.) were bioequivalent to Natrilix®, according to the rate and extent of absorption. Copyright © 2014 John Wiley & Sons, Ltd.